Unraveling diarrheal disease knowledge, understanding, and management practices among climate change vulnerable coastal communities in Ghana - Boafo, Yaw Agyeman; Ohemeng, Fidelia N. A.; Ayivor, Jesse; Ayitiah, Joseph Armah; Yirenya-Tawiah, Dzidzo; Mensah, Adelina; Datsa, Cecilia; Annang, Ted Yemoh; Adom, Lois (Frontiers in Public Health, 2024)
Introduction Diarrheal disease is a global public health concern, particularly in low-income countries. In Ghana, widespread issues like inadequate sanitation, unsafe drinking water, malnutrition, and poor hygiene practices contribute to the high incidence of diarrhea. Climate change exacerbates these challenges by increasing the frequency and severity of conditions that spread diarrheal diseases. This study explores households’ knowledge, understanding, and management practices for diarrhea in climate change-vulnerable coastal communities. Methods The study is set in Ghana’s central (Mumford, Opetekwei) and eastern (Anyako, Anyanui-Atiteti) coastlines. Using a cross-sectional study design, a structured questionnaire was administered to randomly sampled households (n = 419) to collect quantitative data. The study collected qualitative data from focus group discussions (n = 8), with groups separated into men and women, key informant interviews, and observations of food, water, and sanitation conditions across the studied communities. Results and discussion The study found significant variations between the studied communities and socio-demographic variables except for the respondents’ gender. Multivariate regression analyses identified significant associations between socio-demographic variables (especially gender and educational status) and perceptions of diarrhea causes. The most used first management action against diarrhea is ‘over-the-counter drugs’, followed by home-made traditional remedies. Significant differences were observed in the usage of management practices across the studied communities. Trust, affordability, and availability were identified as the main factors influencing households’ use of approved pharmaceutical drugs and traditional herbal remedies for managing behavior, with significant differences being observed across communities. The study recommends a multi-sectoral approach, including improved access to regularly flowing, safe water and sanitation facilities, education on preventing diarrhea, and adequate healthcare services. Community-based interventions such as promoting good hygiene practices at homes and community settings such as schools, lorry parks, funeral grounds, and recreational areas can also effectively reduce the burden of diarrhea.